Palladium‐Catalyzed Enantioselective Redox‐Relay Heck Alkynylation of Alkenols To Access Propargylic Stereocenters. (3rd May 2017) - Chen, Zhi‐Min; Nervig, Christine S.; DeLuca, Ryan J.; Sigman, Matthew S.
Abstract: An enantioselective redox‐relay Heck alkynylation of di‐ and trisubstituted alkenols to construct propargylic stereocenters is disclosed using a new pyridine oxazoline ligand. This strategy allows direct access to chiral β‐alkynyl carbonyl compounds employing allylic alcohol substrates in contrast to more traditional conjugate addition methods.